Pengaruh Pendampingan Ibu Nifas terhadap Risiko Kejadian Depresi Postpartum di Praktik Mandiri Bidan Kota Surabaya - Syuhrotut Taufiqoh; Nova Elok Mardliyana; Umi Ma'rifah; Irma Maya Puspita (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  The postpartum period is the period experienced by women after the baby is born until the reproductive organs return to normal conditions as before pregnancy within six weeks. During the postpartum period, there are several phases of a woman's adjustment to her role as a new parent which can cause anxiety, especially for women who are giving birth for the first time because they do not have experience caring for babies. A mother who cannot adjust to her role as a parent can experience psychological disorders with various symptoms known as postpartum depression. Postpartum depression is a severe and persistent mood change experienced by a woman after childbirth and can last for several months or even a year or more. Methods:  This study is a quantitative study with a quasi-experimental design through pre and post-measurements in the intervention group and control group. The intervention carried out for postpartum mothers was assistance four to 4 times by midwives and in the control group, services were provided according to the standards of postpartum mother visits.Results:  The results showed that the group that was assisted was mostly not at risk for postpartum depression, which was 64%, while the control group did not receive assistance. Most of them are at risk of postpartum depression, which is 72%. And based on the results of the Independent Sample T-Test, it was found that the value of p = 0.012 (<0.05) means that there is an influence of mentoring on the risk of postpartum depression.Conclusion:  Mentoring given to postpartum mothers affects the incidence of postpartum depression risk, where postpartum women who are assisted tend not to be at risk of postpartum depression, and mothers who are not assisted tend to be at risk of postpartum depression.